HUBUNGAN KESELAMATAN KERJA, KESEHATAN KERJA DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN - Elvie Maria; Sukiman Sukiman (Universitas Methodist Indonesia, 2021)
This study aims to determine and analyze the relationship between workplace safety, work health, and job satisfaction on employee productivity. The population and sample in this study were 97 employees of the Malibu Management Agency (BPM), using the census method and the variables of this study were work safety, work health, job satisfaction, and employee productivity. Analysis of the data used is multiple linear regression analysis and using SPSS. The results show that workplace safety, health, and job satisfaction have a strong and direct positive relationship to clarify employee productivity with a contribution of 73.1%. And explained that work safety, work health, and job satisfaction awarded to an employee simultaneously had links and real impact on the productivity of employees.